Waste Management in Areas along the Kathmandu Valley Ring Road in Nepal - Abhiniti Sah; Khatraj Daha (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2023)
Solid Wastes are discarded wastes and are generated from different sources such as sludge from a waste water treatment plant, water supply treatment plant or air pollution control facility and other discarded materials, business and industries, agricultural and community activities. Similarly, urban slums are the result of the rowing pace of urbanization and lack of affordable housing. Managing solid waste in the urban slum area is a major issue concerning Municipal Solid Waste Management. Poor sanitation, drainage and garbage disposal systems degrade the environment which results in hazards both to the physical and mental health of people living in slums area. The research was conducted during the period of 20 Slums areas within the ring road of Kathmandu Valley of Nepal. Field observation, In-depth interviews, focus group discussion and Questionnaire survey were the major instruments used during the investigation. The problems caused due to improper solid waste management in a slum area within the ring road of Kathmandu city have increased in loss of aesthetic beauty and tourism industry, people’s attitude and behaviors and as well as flooding/inundation during monsoon season (RII=0.71) for the people living there. The cause of an inadequate number of waste-collecting vehicles is the insufficient budget (RII=0.71). The cause of the loss of aesthetic beauty is due to the dumping of solid waste in the streets and bank of rivers (RII=0.71). The cause of negative impact on public health is due to the dumping of solid wastes in streets and on banks of rivers, with no strict action for open dumping and burning of the wastes (RII=0.71). The cause of the emission of greenhouse gases is due to methane release from landfill sites (RII=0.72). The study would like to suggest that the government should come up with proper plans and policies along with the enforcement and strict monitoring of the prevailing rules and regulations. Planning should be conducted at every stage and tracking should be done